Jadelle implant acceptance amongst women in Western Health Region 1, The Gambia - Jainaba Sey-Sawo; Haddy Tunkara-Bah (Elsevier, 2018)
The reproductive health hazards of unwanted pregnancies and unsafe abortions have been reduced with modern contraceptive use. The study aimed to highlight the Jadelle Implant acceptance rate amongst women in The Gambia. A descriptive correlational (retrospective) study design was employed. Family planning records were reviewed from January 2015 to December 2015. Data was analyzed using SPSS version 21. Ethical approval was granted by the Regional Health Office, Ministry of Health & Social Welfare, and the Bundung Maternal & Child Health Hospital. Results indicated that out of 3439 acceptors of family planning methods for the year 2015, 660 women went in for the Jadelle implant representing an overall acceptance rate of 19.19%. The mean age was 29.5 years (SD ± 6.3). Mean parity was 4.5 (SD ± 2.4), the average number of alive children was 4.2 years (SD ± 2.1) and most acceptors were housewives 638 (96.7%). A positive relationship existed between age of the last child delivered and Jadelle uptake (p < 0.05). The age of last child delivered was able to predict about 26.1% of Jadelle uptake (p < 0.05). Therefore, the Jadelle implant is a highly accepted contraceptive amongst women attending these health facilities, thus, reducing unintended pregnancies, unsafe abortion, and short birth intervals amongst women in Western Health Region1, The Gambia. Keywords: Jadelle implant, Acceptance, Contraceptives, Women, The Gambia